Characterization of chicken eggshells waste as oil adsorbent by using Scanning Electron Microscope (SEM), Electron Dispersion Spectroscopy (EDS) and Fourier-Transform Infrared Spectroscopy (FTIR): a review - Hasrin, Noradriana Izzaty; Othman, Siti Amira (Asian Scholars Network, 2020)
Nowadays, petroleum products and their derivative constitute have received high demand in order to meet this modern world necessity in the context of advanced and growing industrialization. Somehow, they also have become one of the major sources that causes pollution to the atmosphere, lithosphere, hydrosphere, and biosphere when oil spills accidents occurred. Therefore, various methods have been developed to resolve this problem such as adsorption. Chicken eggshells waste is one of the natural materials that is being used as adsorbent that is effective and low-cost material. In this review paper, the chicken eggshells are characterized in the form of powder by using three instruments which are Scanning Electron Microscope (SEM), Electron Dispersion Spectroscope (EDS), and Fourier-Transform Infrared Spectroscopy (FTIR). This technique is used in order to observe the porosity and surface areas and also the chemical compositions and functional groups in the chicken eggshells.